Comparisons of sweet corn varieties in "cerrado" soils - Tanaka, T.; Lobato, E.; Soares, W. V.; França, G. E. de (Pesquisa Agropecuaria Brasileira, 2014)
A variety test with sweet corn was conducted in three distinct areas of Planalto Central (Brazil). These areas are separated by about 600 km, specifically: Matão, state of São Paulo; Sete Lagoas, state of Minas Gerais; and in two localities, Tamanduá and Planaltina close to Brasília (Federal District). In São Paulo the experiment was established on old crop land, but in Minas Gerais and in the Federal District virgin soils covered previously by scrub savannah were used; lime and fertilizer, including macro and micro-nutrients were added at all locations. The experiment included three local varieties: Amarelo, Branco and Cubano, and three others introduced from the U.S.A.; Sugar & Gold, Sweetangold and Golden Cross Bantam. High levels of production were obtained at all locations as compared with those reported in California, U.S.A. The imported varieties appeared to be less resistant to local pests, but evidenced a great potencial in view of its earliness.